2010
DOI: 10.1074/jbc.m109.024620
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Oligomers of Stefin B and Amyloid-β in Vitro and in Cells

Abstract: To contribute to the question of the putative role of cystatins in Alzheimer disease and in neuroprotection in general, we studied the interaction between human stefin B (cystatin B) and amyloid-␤-(1-40) peptide (A␤). Using surface plasmon resonance and electrospray mass spectrometry we were able to show a direct interaction between the two proteins. As an interesting new fact, we show that stefin B binding to A␤ is oligomer specific. The dimers and tetramers of stefin B, which bind A␤, are domain-swapped as j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…ThT fluorescence and transmission electron microscopy (TEM) have shown that Y31 isoform completely inhibits Aβ peptide fibril formation ( Figure 9I). The direct interaction between those two proteins has also been shown by SPR measurements, where concentration dependent interaction has been reported and by ESI MS where the complex between dimer stB and monomer Aβ peptide has been detected ( Figure 9II) [38]. Furthermore, isolated oligomers of the wild type protein have been studied and it was shown that only the tetramer inhibits Aβ peptide fibril formation and that the higher oligomers show only a weak inhibition.…”
Section: Interaction Between Oligomers Of Stefin B and Aβ Peptide In mentioning
confidence: 94%
See 4 more Smart Citations
“…ThT fluorescence and transmission electron microscopy (TEM) have shown that Y31 isoform completely inhibits Aβ peptide fibril formation ( Figure 9I). The direct interaction between those two proteins has also been shown by SPR measurements, where concentration dependent interaction has been reported and by ESI MS where the complex between dimer stB and monomer Aβ peptide has been detected ( Figure 9II) [38]. Furthermore, isolated oligomers of the wild type protein have been studied and it was shown that only the tetramer inhibits Aβ peptide fibril formation and that the higher oligomers show only a weak inhibition.…”
Section: Interaction Between Oligomers Of Stefin B and Aβ Peptide In mentioning
confidence: 94%
“…It exhibits nearly all features shared with other amyloid forming proteins: it forms mature fibrils under mildly acidic conditions or even at neutral pH at somewhat higher temperature, forms membrane pores and therefore promotes membrane leaking, binds copper ions and its' oligomers are toxic. It is not a model protein only, but also could be termed an "amateur chaperone" affecting Aβ peptide fibril formation both in vitro and in vivo [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations